Community Adaptation in Facing the Digital Governance - Syahruddin; Nur Jalal; David Laiyan; Dapot Pardamean Saragih; Hubertus Oja; Erwin Nugraha Purnama; Syaharabudin Husein Enala (Technium Social Sciences Journal, 2023)
In an increasingly digitally connected era, governments and private organizations continue to move towards implementing digital governance to improve service efficiency, transparency, and responsiveness. This digital transformation process has had a significant impact on society. The adoption of information and communication technology has changed the way society interacts with governments, companies, and fellow community members. Therefore, community adaptation is an important key in facing this change. The purpose of this study is to describe how society adapts to changes due to the adoption of digital governance. This research uses qualitative methods by collecting data through in-depth interviews and content analysis from reliable sources. An interdisciplinary approach is used to look at social, economic, and political aspects in the process of community adaptation. The results show that people’s adaptation to digital governance involves a number of challenges and opportunities. On the positive side, the adoption of technology has accelerated access to information and public services, increased public participation in decision-making processes, and empowered specific community groups. However, there are also negative impacts such as the digital divide, data security issues, and inequality of technology access that affect some groups of society. This research highlights the importance of digital literacy and inclusion in helping society adapt to these changes. Strengthening education and training in the use of technology will help reduce the digital divide and increase people’s active participation in digital governance.